How Does Organization Network and Market Orientation Affect Marketing Performance? Case of PTPN IX Downstream Products, Central Java - Wahyudi, Wahyudi; Heridiansyah, Jefri; Susetyarsi, Theresia; Safari, Teti; Prabowo, Catur (Universitas Negeri Semarang, 2024)
This study aims to determine the effect of organizational network and market orientation on marketing performance on downstream products of PTPN IX Central Java. The sample is 34 respondents with a nonprobability sampling technique using the census method. The independent variables in this study are organizational networks and market orientation, then the dependent variable is marketing performance. The data collection method used in this study is a questionnaire. The data analysis method used is descriptive analysis and multiple linear regression analysis. Based on the research results, organizational networks positively and significantly affect marketing performance. The market orientation has a positive and significant effect on the marketing performance of downstream products of PTPN IX in Central Java. Marketing performance impacts sales turnover, sales increase and marketing reach. Therefore, management must pay attention to every relationship, whether friends, business relations or partner companies, both large and small, and fulfill customer orientation, threats from competitors, and market information.